RETURN FROM UTOPIA: THE MONTALDO COLLECTION AND THE END OF THE ICARIAN DREAM - Jordi Olivar; José Miguel Lemus (European Scientific Journal, ESJ, 2015)
In 1848, Étienne Cabet moved to the United States with several hundred followers to implement the utopian society he had envisioned in Voyage en Icarie (1840)in American soil. Among the followers of Cabet, there were some Catalans such as Narcís Monturiol, Francisco José de Orellana, Joan Rovira, and Ignacio Montaldo. Rovira and Montaldo joined Cabet in his travel to America from Europe in 1848. In 1992, a retired librarian from Harvard University reported the existence of letters and documents "to and from" Ignacio Montaldo. Copies of these letters, written mainly in French and Spanish, are currently held at the Icarian Studies Center at Western Illinois University. To our knowledge, the letters have not been transcribed, translated or published. This may be attributed to difficulty to understand the letters due to the physical conditions of the documents. The main contribution of this article is the translation into English of the letters of the Montaldo Collection written in Spanish. (1) Finally, the content of these letters will reveal the particular impact that the defeat of the Spanish liberal project of the Progressive Biennium (1854-1856) had for Spanish Icarians.